Introduction to the Special Issue: Scripting Fat Television. Issue 1 (2nd January 2021) - Farr, Daniel
ABSTRACT: In this introduction to the special issue on Scripting Fat Television, the author highlights the important role television plays in contemporary culture and denotes the importance of expanding critical examination of fat imagery, particularly as it appears in scripted television programs. The production of these shows simultaneously reproduces and challenges cultural ideologies about fat and fat embodiment. As more programs centering upon or inclusive of fat experience are produced, analyses and critiques of these depictions enrich the understanding of not only the discourse of body and identity, but also challenge the audience to more deeply engage with their interactive experience of television imagery.